URBAN MUSLIM HOUSEHOLDS: HOW SHARIA CONSUMPTION LOYALTY AND SHARIA FINANCIAL LITERACY SHAPE LIFE SATISFACTION - Setiawan, Setiawan; Fransiska, Alda Tri; Pebrianti, Gita Nuralipah; Pakpahan, Rosma; Susana, Lina Marlina (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2025)
This study aims to analyze the influence of loyalty in Sharia-compliant consumption patterns and sharia financial literacy on the life satisfaction of urban Muslim households in the Greater Bandung area. A quantitative approach was employed, using a survey method through online questionnaires distributed to 160 Muslim households with experience or knowledge related to Sharia-based consumption and finance. The sampling technique used was purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), which is suitable for complex structural models with moderate sample sizes and non-normally distributed data. The results indicate that both loyalty in Sharia-compliant consumption and sharia financial literacy have a positive and significant effect on the life satisfaction of urban households. These findings highlight the critical role of religious values and Sharia-based financial management capabilities as determinants of subjective well-being among urban Muslim families.